Development of bio-adhesives for composites wood using natural rubber latex and modified starch with crosslinkers - Triveni, Soubam (2022)
Synthetic adhesives used in the composite wood industries are a matter of concern due to the emission of carcinogenic gas formaldehyde, increased environmental pollution and the depletion of fossil fuels. Therefore, developing a formaldehyde free and eco-friendly adhesive derived from renewable resources is essential. The present research focuses on developing and applying bio-adhesives based on two biopolymers: crosslinked rice starch (RS) and natural rubber latex (NRL). The rice starch was crosslinked with glyoxal, polymeric 4,4”- diphenylmethane diisocyanate (pMDI), and dimethylol dihydroxy ethylene urea (DMDHEU) to improve its hydrophilicity nature before blending with NRL. The chemical interaction of rice starch and crosslinkers was investigated using attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). The hydrophobicity of native rice starch and crosslinked rice starch was measured using contact angle measurements. By blending, a bio-adhesive with varying weight content of crosslinked RS and NRL was developed, and its physical properties such as gel time, viscosity, and solid content were characterized. Consequently, formulated bio-adhesives were applied for plywood manufacturing via hot pressing at 120°C for 5 minutes, and plywood specimens were characterized physically and mechanically in terms of water absorption (WA), thickness swelling (TS), modulus of rupture (MOR), modulus of elasticity (MOE) and internal bonding (IB). The thermal stability and surface property of the plywood were observed through thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The physical and mechanical properties of the plywood are measured following ASTM, ISO, and IS standards. The design expert software DX7 was used to examine the significant variables that influence bio-adhesive formulations in plywood internal bonding. ATR-FTIR confirmed the presence of glyoxal, isocyanate, and DMDHEU functionalities in starch macromolecules, resulting in enhanced bio-adhesive performance. The glyoxal crosslinked starch, has outstanding hydrophobic nature, with an CA of 91.45° at 3 minutes. The bio-adhesive Iso A was discovered to have the highest viscosity of 8270 mPa.s. The bio-adhesive type Gly B has the shortest gel time of 2.80 min and the highest solid content of 46%, the higher the solid content, the faster the gel time. The plywood bonded with Gly B bio-adhesive shows the lowest thickness swelling (TS) of 11% and water absorption (WA) of 35%. Plywood bonded with Gly B bio-adhesive had the highest modulus of rupture (MOR) of 72 MPa, modulus of elasticity (MOE) of 9574 MPa, and internal bonding (IB) of 2.2 MPa corresponded to the ISO 12466-2-2007 and IS 303 standard requirements. Furthermore, the thermal analysis showed that plywood bonded with Gly A bio-adhesive has a higher weight loss temperature, indicating that the addition of crosslinked rice starch improves the oxidative thermal stability of bio-adhesive. As for the surface property, the plywood bonded with Gly B showed less void and visible patches in a random distribution in between the wood fibres matrices. Based on the RSM-CCD regression model, the ideal parameters of bio-adhesive formulation that influence the internal bonding of plywood were 73.47°C, pH 7.33, and 0.35% glyoxal. According to the findings, the plywood bonded with Gly B bio-adhesive significantly impacted the quality of adhesion properties compared to other bio-adhesive formulations. This study shows that biopolymers like crosslinked rice starch and NRL can help to eliminate the use of hazardous synthetic adhesives completely.